E-Accounting Practices among Small and Medium Enterprises in Ghana - Amidu, M.; Effah, J.; Abor, J. (My University, 2011)
This study explores the e-accounting practices among SMEs in Ghana. The study also looks at the expectations, realities and barriers in adopting e-accounting. The research design is based on a survey methodology using a sample of systematically selected SMEs throughout the country. The findings reveal that SMEs put in place accounting softwares to generate their financial information. The main value of this paper is the discussion of e-accounting practices of SMEs in Ghana.